The labor market in Switzerland, 2000-2016 - Rafael Lalive; Tobias Lehmann (IZA World of Labor, 2017)
Switzerland is a small country with rich cultural and geographic diversity. The Swiss unemployment rate is low, at only about half the OECD average. The rate has remained at that level since the year 2000, despite a massive increase in the foreign labor force, the Great Recession, and a currency appreciation shock, demonstrating the Swiss labor market's impressive resiliency. However, challenges do exist, particularly related to earnings and employment gaps among foreign and native workers, as well as a narrowing but persistent gender pay gap. Additionally, regional differences in unemployment are significant.
Keywords: 330; unemployment; real earnings; labor force participation; Switzerland